(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: Staphylococcus aureus and Escherichia coli are the most common opportunistic pathogens frequently associated with respiratory tractinfection (RTI) in different animals. This cross-sectional study aimed to identify the occurrence of S. aureus and E. coli in goats with RTI, analyze the antimicrobial resistance patterns, and explore potential risk factors contributing to RTI. Materials and Methods: A total of 120 nasal swab samples were collected from goats, and standard classical bacteriological methods were performed to isolate and identify S. aureus and E. coli. Subsequently, the disc diffusion method was employed to evaluate the antimicrobial sensitivity test. A logistic regression model was used to analyze the factors associated with RTI. Results: About 13.3% (N = 16; N = 120) isolates were confirmed as S. aureus, and 6.67% (N = 8; N = 120) isolates were confirmed as E. coli. All S. aureus isolates were resistant to ampicillin, and all E. coli isolates were resistant to amoxicillin and penicillin. Among the isolated organisms, 43.7% (N = 7; N = 16) S. aureus and 62.5% (N = 5; N = 8) E. coli isolates were found to be multidrug-resistant (resistant to ≥3 classes of antimicrobials). Multivariable logistic regression analysis revealed that female goats [(odds ratio) OR: 4.2; 95% confidence intervals (CI): 0.8–20.8; p = 0.074] and goats in poor health condition (OR: 3.8; 95% CI: 0.7–19.3; p = 0.100) were more prone to RTI caused by S. aureus. Besides, goats that were not dewormed (OR: 4.8; 95% CI: 1–23.6; p = 0.051) and those reared in semi-intensive conditions (OR: 2.7; 95% CI: 0.8–8.7; p = 0.092) were found to be at higher risk of S. aureus-mediated RTI. Conclusion: The findings highlight the importance of implementing improved farm management practices and efficient antimicrobial resistance control approaches to minimize respiratory infections and reduce the burden of antibiotic resistance in goats. J. Adv. Vet. Anim. Res., 11(4): 1037–1050, December 2024 http://doi.org/10.5455/javar.2024.k855